Arab Republic of Egypt : Poverty Assessment Update, Volume 1. Main Report - World Bank (Washington, DC, 2012)
This report on the Poverty Assessment Update of Egypt is a contribution to the strategy of poverty alleviation pursued by the Government of Egypt. Using data from the two household surveys in 2000 and 2005, this report assesses the nature and dimensions of poverty in Egypt, and discusses the role of macroeconomic policies and labor markets in improving living standards. The report updates the findings of "Poverty Reduction in Egypt: Diagnosis and Strategy," published by the World Bank in 2002. Over the last two years Egypt has achieved remarkably high economic growth. Should this turnaround be sustained, there is hope that poverty can be dramatically reduced. Even though the report does not cover this most recent period, it is important to learn from the lessons of the recent past, and the report provides new information and insights that could be useful for policy-makers: 1) It identifies the overall scope and trends in poverty between 2000 and 2005, focusing on material aspects, but also assessing progress in non-income dimensions; 2) It isolates key correlates to poverty and economic vulnerability, providing detailed analysis of how inflation affected the poor in this period; 3) It links the labor market's developments with changes in living standards and poverty; and 4) It provides the analytical base for mapping poverty in Egypt, which can improve the targeting of social programs. The first chapter examines the evolution of living standards in Egypt during the period of analysis - 2000 to 2005. It also gives the details of the poverty map and where the poor live. Chapter 2 describes who the poor are and provides the poverty correlates: looking at the characteristics of the poor and the relation of these characteristics to education (and access to education), employment, gender, age, or asset characteristics. Chapter 3 continues by providing some background on economic developments between 2000 and 2005 and identifies possible areas of policy interventions in light of economic and social policies and developments after 2005. Chapter 4 offers in-depth analysis of the labor market to attempt to discern longer-term trends in living standards, and links employment with poverty levels. Finally, Chapter 5 looks at the capacity of the monitoring system, and lays the foundations for a future analytical program.